The Influence of the Use of Audiovisual Animation Media on Student Behavior in Earthquake Mitigation at SMPN 1 Pancur Batu - Putri Ulandari; Ajeng Andini; Susilawati Susilawati; Nabila Andini; Wafida Tunnur Siregar (PROMOTOR, 2026)
SMPN 1 Pancur Batu is a school located in an earthquake-prone area, but it does not yet have structured earthquake mitigation facilities and learning programs. This condition can be seen from the students' low understanding of safety measures during an earthquake and the lack of safety promotion media such as posters or other educational tools. Some students also do not understand basic actions such as the Drop, Cover, and Hold On principle, and there are no regular earthquake mitigation education activities conducted at the school. This study aims to examine the effect of audiovisual animation media on earthquake mitigation behavior among ninth-grade students. The research method used an experimental design with a “One Group Pretest–Posttest Design” and involved 50 students selected using purposive sampling. The results of the study showed a significant increase in mitigation behavior, with 48 students (96%) experiencing an increase in scores after being given an intervention in the form of earthquake education animation. Based on the results of the Wilcoxon Signed-Rank Test nonparametric test, a p-value < 0.001 (p < 0.05) was obtained, which means that there is a significant effect between the use of audiovisual animation media and students' earthquake mitigation behavior. Thus, it can be concluded that audiovisual animation media is effective in improving students' knowledge, attitudes, and actions in dealing with earthquakes. The suggestion given is the need for regular disaster education in collaboration with the Regional Disaster Management Agency (BPBD) or related agencies so that students' preparedness can be improved and applied in real situations.